The Interplay of Destructive Work Behaviors, Organizational Citizenship Behaviors, and Fiscal Decentralization: Implications for Economic Development in Developing Countries - Farzad, Golnaz; Roshdieh, Nasim (AI and Tech in Behavioral and Social Sciences, 2025)
This paper investigates how destructive work behaviors, Organizational Citizenship Behaviors (OCBs), and fiscal decentralization intersect in developing countries’ economic development. Corruption and inefficiency in decentralized systems hinder governance and economic growth, while altruism and conscientiousness in organizations foster transparent, collaborative cultures. Giving more power to local governments through fiscal decentralization can lead to better service delivery and meeting the needs of the community, as long as negative behaviors are minimized, and organizational citizenship behaviors are promoted. The essay highlights the significance of focused interventions like anti-corruption efforts and ethics training to improve governance integrity and promote sustainable economic growth.